The impact and role of hepatic hydrothorax in the prognosis of patients with decompensated cirrhosis: A retrospective propensity score-matched study - Ma, Bo; Shang, Tianling; Huang, Jianjie; Tu, Zhixin; Wang, Yan; Han, Yujin; Wen, Xiaoyu; Jin, Qinglong (Frontiers in Medicine, 2022)
.Background and aims: Hepatic Hydrothorax (HH) is one of the complications in patients with decompensated cirrhosis and its impact and role in the prognosis of patients with decompensated cirrhosis are not yet clear. Thus, this study aimed to determine the role of HH in patients with decompensated cirrhosis and the long-term impact on their mortality. Methods: A retrospective study analyzed 624 patients with ascites without pleural effusion in decompensated cirrhosis and 113 patients with HH. Propensity scores were calculated based on eight variables, and the HH and non-HH groups were matched in a 1:1 ratio. The effect and role of HH on the prognosis of patients with decompensated cirrhosis was analyzed using the Kaplan–Meier method and Cox proportional hazards regression model. Results: A total of 737 patients were included. Out of 113 HH patients, 106 could be matched to 106 non-HH patients. After matching, baseline characteristics were well balanced. The multifactorial Cox proportional hazards model indicated that hepatic encephalopathy and HH were independent risk factors affecting prognostic survival in patients with decompensated cirrhosis (P < 0.01), with risk ratios and 95% confidence intervals (CI) of 2.073 (95% CI: 1.229–3.494, P < 0.01) and 4.724 (95% CI: 3.287–6.789, P < 0.01), respectively. Prognostic survival was significantly worse in the HH group compared to patients in the non-HH group, with mortality rates of 17.9%, 30.1%, and 59.4% at 6 months, 1 year, and 2 years in the HH group, compared to 0.9%, 3.8%, and 5.6% in the non-HH group, respectively. The estimated median survival time was 21 (95% CI: 18–25) months in the HH group and 49 (95% CI: 46–52) months in the non-HH group (P < 0.001). Conclusion: HH is significantly associated with higher mortality in patients with decompensated cirrhosis and is a highly negligible independent decompensated event affecting their prognosis.